High carbon containing biomaterial offering honeycomb morphology as a charge storing electrode in aqueous alkaline electrolytes - Bindhu, Devu; Sreekala, Chandrasekharannair Omanaamma; Nurulhuda, Mohamed Shah; Ling, JinKiong; Izan Izwan, Misnon; Yang, Chun-Chen; Jose, Rajan (Elsevier, 2024)
Research on unconventional carbon structures and morphologies obtainable from renewable sources are a way forward in realizing sustainable materials for the next-generation industry. Herein, renewable porous carbon from a biomass (coconut rachis) with high carbon content (∼81 %) and honeycomb morphology (inner diameter ∼60 μm and wall thickness ∼500 nm) is developed as an electrochemical capacitor electrode. The coconut rachis upon chemical activation yield a surface area ∼1,630 m2‧g−1 and desirable pore characteristics for storing aqueous cations. The electrochemical charge storability of the porous carbon electrodes in 1 M KOH, NaOH and LiOH electrolytes showed specific capacitances ∼320, ∼140 and ∼102 F‧g−1, respectively. Electrochemical impedance spectra validated the higher capacitance in the KOH electrolyte. Besides, symmetric supercapacitor full cells were fabricated using the present electrode in 1 M KOH electrolyte with desirable charge storage properties. Given the abundance of the precursor and desirable charge storage characteristics, the present work could be useful in developing the coconut rachis-resourced honeycomb-shaped porous carbon as a charge storing electrode.